MIG welding of dissimilar metal using different thicknesses (aluminum and mild steel) - Muhamad Fadhli, Zainuddin (2012)
In this project, the main objective is to study the optimum thickness ratio of the different material combination joint and also weld joint‘s quality on the various gauge ratios and the defect. Tailor welded blanks (TWBs) of combinations different material and with various of thickness were weld by using Metal Inert Gas (MIG) welding before do the test. Thus aluminum AA1100 with thickness 1, 2, 3, and 4 mm and mild steel with thickness 2, 3, and 4 mm were studies and combination to form TWBs of different thickness ratios of 0.33 (1/3 mm), 0.5 (1/2 mm), 0.66 (2/3 mm), 0.25 (1/4 mm), 0.5 (2/4 mm) and 1.5 (3/2 mm). The joint were evaluated by mechanical testing and metallurgical analysis. Microstructural analyses were done by using metallurgical microscopic and also Vickers hardness testing and tensile testing were used to investigate optimum gauge ratio. The fracture in tensile tests occurred at the interfacial layer of the aluminum-mild steel joint layer zone. Result of this analysis find that 0.33 gauge ratio is optimum gauge ratio with maximum force 1670 N. the factor that effect of maximum force joint is intermetallic layer. in microstructural analysis the hardness for mild steel will increase at heat affected zone (HAZ), while hardness of aluminum will decreases at HAZ. During the experiment, some of defects were found at specimen such as spatter, incomplete fill and porosity but the best specimen only used for experiment.